1999
DOI: 10.1038/sj.neo.7900061
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of p53 Mutations to Epidermal Cell Proliferation and Apoptosis in Human UV-Induced Skin Carcinogenesis

Abstract: Human skin is continually subjected to UV-irradiation with the p53 gene playing a pivotal role in repair of UV-induced DNA damage and apoptosis. Consequently, p53 alterations are early events in human UV-induced skin carcinogenesis. We studied 13 squamous cell carcinomas (SCC), 16 actinic keratoses (AK), 13 samples adjacent to an AK (chronically sun-damaged), and 14 normal-appearing skin samples for p53 mutation, p53 immunostaining (IHC), apoptosis (in situ TUNEL and morphology), and proliferation (PCNA). The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
69
2
4

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(82 citation statements)
references
References 37 publications
6
69
2
4
Order By: Relevance
“…50 In addition, it has been shown that epidermal cell proliferation was significantly increased in the progression from normal skin to squamous cell carcinoma. 50,51 Thus, UV-induced proliferation of both basal and suprabasal keratinoctyes enables mutations to be established and may contribute to initial process of tumorigenesis. Similarly in our study, both basal and suprabasal keratinocytes in UV-irradiated EHS were Ki-67 positive, indicating that they were dividing.…”
Section: Discussionmentioning
confidence: 99%
“…50 In addition, it has been shown that epidermal cell proliferation was significantly increased in the progression from normal skin to squamous cell carcinoma. 50,51 Thus, UV-induced proliferation of both basal and suprabasal keratinoctyes enables mutations to be established and may contribute to initial process of tumorigenesis. Similarly in our study, both basal and suprabasal keratinocytes in UV-irradiated EHS were Ki-67 positive, indicating that they were dividing.…”
Section: Discussionmentioning
confidence: 99%
“…For example, E2F1 is known to be induced by cytotoxic stimuli and DNA damage (7,8). This induction can occur at the level of post-translational modification and protein stabilization and/or can occur through increased E2F1 transcription (16,38). The main outcome of the increased E2F activity is mediated via ARF stimulated inhibition of MDM2 resulting in increased p53-dependent apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…For example, disruption of the Rb/E2F axis is common in almost all human cancers including SCC [36]. Loss of function mutations of p53, Rb, or upstream regulators of the Rb/E2F axis such as INK4A (p16) are frequently associated with SCC and may result from mutation, deletion or promoter hypermethylation [37][38][39]. Moreover, SCCs are frequently associated with amplification/activation of mitogenic pathways controlled by cyclin D1, cdk4 or EGFR [31,40].…”
Section: Role Of Uv In Skin Carcinogenesismentioning
confidence: 99%
“…p53 is the key UV-responsive gene in skin, whose mutation is thought to initiate carcinogenesis, but its role in the control of keratinocyte proliferation and differentiation is less clear (26,34). Epidermal keratinocytes are most susceptible to damage from UV light, because they are close to the skin surface.…”
Section: P53 Regulation In Keratinocytes and In The Epidermismentioning
confidence: 99%
“…p53 is mutated or deleted in more than 50% of human tumors and in most skin carcinomas (22,(24)(25)(26)(27)(28). As regards UVinduced skin tumors, p53 is considered to play an important role in their pathogenesis (29,30).…”
Section: P53 Regulation In Keratinocytes and In The Epidermismentioning
confidence: 99%